Cortex Mori extracts induce apoptosis and inhibit tumor invasion via blockage of the PI3K/AKT signaling in melanoma cells - Hu, Xin; Zhang, Kui; Pan, Guangzhao; Wang, Yinggang; Shen, Yue; Peng, Cheng; Deng, Longfei; Cui, Hongjuan (Frontiers in Pharmacology, 2022)
Melanoma, the most aggressive and deadliest form of skin cancer, has attracted increased attention due to its increasing incidence worldwide. The Cortex Mori (CM) has long been used as a classical traditional Chinese medicine (TCM) to treat various diseases, including cancer. The bioactive components and underlying mechanisms, however, remain largely unknown. The current study aims to investigate the anti-melanoma effects of CM and potential mechanisms through combined network pharmacology and bioinformatic analyses, and validated by in vitro and in vivo experiments. We report here that CM has anti-melanoma activity both in vitro and in vivo. Furthermore, 25 bioactive compounds in CM were found to share 142 melanoma targets, and network pharmacology and enrichment analyses suggested that CM inhibits melanoma through multiple biological processes and signaling pathways, particularly the PI3K-AKT signaling inhibition and activation of apoptotic pathways, which were further confirmed by biochemical and histological examinations. Finally, partial CM-derived bioactive compounds were found to show anti-melanoma effects, validating the anti-melanoma potential of bioactive ingredients of CM. Taken together, these results reveal bioactive components and mechanisms of CM in inhibiting melanoma, providing them as potential anti-cancer natural products for the treatment of melanoma.